Water-energy relationships shape the phylogenetic diversity of terricolous lichen communities in Mediterranean mountains: Implications for conservation in a climate change scenario. (December 2022) - Vallese, Chiara; Di Musciano, Michele; Muggia, Lucia; Giordani, Paolo; Francesconi, Luana; Benesperi, Renato; Chiarucci, Alessandro; Di Cecco, Valter; Di Martino, Luciano; Di Nuzzo, Luca; Gheza, Gabriele; Zannini, Piero; et al.
Abstract: Lichens are symbiotic organisms sensitive to climate change and susceptible to a severe decline in diversity, especially in high elevation environments that are already threatened. In this study, we focused on water-energy relationships derived from climatic variables and phylogenetic diversity indices of terricolous lichen communities occurring on a representative Mediterranean mountain. We hypothesized that the variation of precipitation and temperature and their interaction along the altitudinal gradient will shape the phylogenetic diversity and structure of lichen communities. Our results reveal that dry and arid conditions lead to a strong loss in phylogenetic diversity with consequent impoverishment of high elevation lichen communities under a climate change scenario. The interaction between variables, reflecting water-energy relationships with phylogenetic and community diversity patterns, suggests that in a future climate change scenario, the novel climatic conditions may reduce the capability of the species to survive harsher conditions, and Mediterranean mountains may face a severe loss of genetic diversity in a climate change scenario.